2018
DOI: 10.1159/000494659
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Virtual Reality-Based Tai Chi Exercise on Cognitive and Physical Function in Older Adults with Cognitive Impairment

Abstract: Background: Tai Chi (TC) is a Chinese mind-body exercise with proven physical and psychological benefits. A modified TC via virtual reality (VR) may be suitable for the elderly owing to the immediate guidance and feedback regarding movement accuracy. This study explored the cognitive and physical effects of a VR-based TC (VRTC) exercise program on older adults with cognitive impairment (CI). Methods: Sixty older adults with CI were cluster-assigned to either the VRTC or the control group; the intervention was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 38 publications
1
61
0
1
Order By: Relevance
“…28 Recent increasing studies showed Tai Chi exercise also had positive effect in improving the global cognitive function and memory, executive ability in older adults with cognitive impairment. 29 A study reported that a 12-week Baduanjin training with 1 hour per day for five days per week could prevent the age-related memory decline in community healthy older adults. 30 Another research revealed that the eight-week Baduanjin training had positive benefit to improve executive domain in a young and healthy population; the mechanism might be due to that the mental process of the Baduanjin exercise involves self-regulation (or self-control of cognitive and emotional processes) as core cultivation, and the executive function shares with the brain circuits of self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…28 Recent increasing studies showed Tai Chi exercise also had positive effect in improving the global cognitive function and memory, executive ability in older adults with cognitive impairment. 29 A study reported that a 12-week Baduanjin training with 1 hour per day for five days per week could prevent the age-related memory decline in community healthy older adults. 30 Another research revealed that the eight-week Baduanjin training had positive benefit to improve executive domain in a young and healthy population; the mechanism might be due to that the mental process of the Baduanjin exercise involves self-regulation (or self-control of cognitive and emotional processes) as core cultivation, and the executive function shares with the brain circuits of self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Exergames have been gradually implemented in rehabilitation [ 37 , 38 ], education [ 39 ], and other fields [ 40 ], and have been widely accepted by a range of populations from children [ 41 , 42 ] to the elderly [ 43 , 44 ]; moreover, positive results were found for individuals with various diseases such as dementia [ 45 ], stroke [ 46 ], Parkinson disease [ 34 ], multiple sclerosis [ 47 ], cystic fibrosis [ 48 ], and cancer [ 49 ]. Recent studies have demonstrated the feasibility, acceptability, and effectiveness of exergaming in improving physical functions such as gait and balance [ 50 ], motion control [ 51 ], and exercise capacity [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies performing verbal fluency or animal name fluency in healthy older adults [25] and in older adults with mild cognitive decline [21,23] did not indicate statistically significant improvements. Other types of executive function measures were used in six studies [19,[21][22][23][24][25]. Dualtask performance during motor and cognitive tasks measured by TUG-cog performed by healthy older adults indicated statistically significant improvement compared to the control group [21] but not TUG-DT performed by older adults with mild cognitive decline [19].…”
Section: Executive Functionmentioning
confidence: 79%
“…The intervention period of the included studies was six-weeks-six-months. Three studies were conducted for six months [17,20,21], two studies were conducted for three months [16,24], one study was conducted for eight weeks [22], one study was conducted for seven weeks [18], and four studies were conducted for six weeks [19,23,25,26]. Three studies used a stationary bike equipped with a VR display ("Cybercycle" or "Cycle-ergometer") as the method of VR-PE [16,17,23].…”
Section: Interventionmentioning
confidence: 99%